UNGASS 2016 WITH THAILAND’S DRUG PROBLEM-SOLVING POLICY - Chantavaro, Kobgoon (Rangsit Journal of Law and Society, 2022)
The drug problem has been damaging and affecting the global community widely. As a result, the United Nations Organization (United Nations Organization) plays a role in preventing and solving such problems by initiating the rules setting the standards and the guidelines using the international forum, the United Nations General Assembly, as a mechanism to prevent and solve the drugs and psychotropic substances issues. In 2016, the United Nations organized the United Nations General Assembly’s special session on the World Drug Problems (UNGASS 2016), to review the criteria, measures, and guidelines, solving drug problems. According to the review, the previous implementations of the strict legal enforcement and the severe punishment are not appropriate for the circumstances, which require the consideration on the public health and humanitarian principles. This is because the majority of the drug addicts are not the problem drug users. Therefore, their health should be treated and they should be able to access to essential medicines under the humanitarian supervision. Hence, the seven resolutions called “Our Shared Commitment to Effectively Manage and Respond to Drug Problems” are initiated, as the new approaches to be implemented by the member states. Thailand sent representatives to attend the UNGASS 2016 with no objection to the General Assembly’s resolution. However, Thailand have neglected the above resolutions, due to the fact that there is no adjustment of the policy, law or practice guidelines in accordance with the aforesaid resolutions during the past four years after the UNGASS 2016 conference. Therefore, Thailand should expedite the concrete adoption of such resolution to become actual implementation.